(untitled) - Pursley, Michael B. (New Jersey, 2005)
This book provides an introduction to the basic concepts in digital communications for readers with little or no previous exposure to either digital or analog communications. The intent is to help learners develop a firm understanding of digital communication system engineering—and to enable them to conduct system-level design and analysis for digital communication systems of the future. As a result, the book emphasizes the basic principles of digital communications theory and techniques, rather than presenting specific technologies for implementation. Chapter topics include probability and random variables—review and notation, introduction to random processes, linear filtering of random processes, frequency-domain analysis of random processes in linear systems, baseband transmission of binary data, coherent communications, noncoherent communications, intersymbol interference, and spread-spectrum communication systems. For individuals preparing for a career in wireless communications system design.
Keywords: Digital communications